Penggunaan Metode RGEC dalam Menilai Tingkat Kesehatan Bank: Suatu Kajian - Hana Tamara Putri; Arna Suryani (Universitas Batanghari Jambi, 2022)
Bank Indonesia perfected the Bank's health assessment method from CAMELS to RGEC method which includes factors of Risk Profile, Good Corporate Governance, Earning, and Capital in accordance with Bank Indonesia Circular Letter No.13/24/DPNP dated October 25, 2011 on Assessment Health Level of Commercial Banks. The results of the analysis on the Rating of Health Level at Bank 9 Jambi using RGEC method shows the bank's health predicate in accordance with the standards set by Bank Indonesia for the period 2015-2019 with the conclusion of the assessment results in composite 2, which reflects the general condition of the bank healthy.